Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/nrdp.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic pain

Abstract: Neuropathic pain is caused by a lesion or disease of the somatosensory system, including peripheral fibres (Aβ, Aδ and C fibres) and central neurons, and affects 7–10% of the general population. Multiple causes of neuropathic pain have been described and its incidence is likely to increase owing to the ageing global population, increased incidence of diabetes mellitus and improved survival from cancer after chemotherapy. Indeed, imbalances between excitatory and inhibitory somatosensory signalling, alterations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
1,364
0
66

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,564 publications
(1,653 citation statements)
references
References 203 publications
11
1,364
0
66
Order By: Relevance
“…The overall prevalence of CC is 9.6% [58] which is similar to the prevalence of neuropathic pain in Australia (8.5%) [59] and in Europe (7–8%) [60]. There are, however, wide regional variations ranging from a high of 18.1% in Oceania down to 2.3% in Africa for CC [58].…”
Section: Introductionmentioning
confidence: 88%
“…The overall prevalence of CC is 9.6% [58] which is similar to the prevalence of neuropathic pain in Australia (8.5%) [59] and in Europe (7–8%) [60]. There are, however, wide regional variations ranging from a high of 18.1% in Oceania down to 2.3% in Africa for CC [58].…”
Section: Introductionmentioning
confidence: 88%
“…Differences between animal behavioural tests and human chronic pain features, particularly the assessment of both sensory and affective features of the pain state, as well as measurements of long-term efficacy and species variability may have been confounding factors (6). Nevertheless the successful translation of the substance Psaporin treatment from rats to companion dogs with bone cancer pain suggests (11,14) there is potential for the introduction of botulinum-based silencing approaches for the control of pain without cytotoxicity or recourse to repeated treatment of analgesics that can produce adverse behavioural effects.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent pain is highly prevalent and extremely difficult to treat (6,7) with widely prescribed drugs such as opioids having significant unwanted side effects (7)(8)(9). While research into developing new analgesic drug therapies has been intense, translating knowledge from preclinical observations in animal models to new therapies in the clinic has been challenging (6). Research into the control of chronic pain states has however identified pathways connecting the spinal cord and brain that are key to the regulation of on-going pain states (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the hallmark symptoms is mechanical allodynia (non-nociceptive mechanical stimuli elicit pain), and neuropathic pain is often resistant to currently available therapies. 1) Injury to peripheral nerves of rodents, which are frequently used as models of neuropathic pain, produces mechanical pain hypersensitivity and alterations at molecular and cellular levels that result in multiple forms of neuronal plasticity and structural reorganization, not only in the affected sensory ganglion cell body, but also in the spinal dorsal horn (SDH). 2,3) The peripheral nerve injury (PNI)-induced alterations in the SDH are observed not only in neurons, but also in glial cells, especially microglia, which are known as resident immune cells in the central nervous system (CNS).…”
mentioning
confidence: 99%